2017
DOI: 10.1089/hum.2017.160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Gene Therapy for Neurodegenerative Diseases: Past, Present, and Future

Abstract: Clinical gene therapy has made important advances over the last decade. Among neurological diseases, severe genetic neurodegenerative conditions have been the focus of initial clinical applications. Gene therapy has also addressed complex neurodegenerative diseases, particularly Parkinson's disease, with encouraging results in human patients, demonstrating that specific targeting of central nervous system (CNS) cells is a relevant strategy for severe pathologies and that efficient access to the CNS with viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 141 publications
0
79
0
1
Order By: Relevance
“…In addition to choice of capsid for safest and most disease-relevant spatial and temporal requirement for transgene expression, alterations to the transgene-coding region and regulatory elements are also common. Most clinical studies currently use high-expressing ubiquitous promoters such as variants of the human cytomegalovirus (CMV) or chicken beta-actin (CBA) promoters with CMV enhancer (CAG) [70]. Variations of this promoter have been characterized extensively and show robust expression throughout neuronal cell types in the CNS [71].…”
Section: Choice Of Aav Capsid Serotype and Promotermentioning
confidence: 99%
“…In addition to choice of capsid for safest and most disease-relevant spatial and temporal requirement for transgene expression, alterations to the transgene-coding region and regulatory elements are also common. Most clinical studies currently use high-expressing ubiquitous promoters such as variants of the human cytomegalovirus (CMV) or chicken beta-actin (CBA) promoters with CMV enhancer (CAG) [70]. Variations of this promoter have been characterized extensively and show robust expression throughout neuronal cell types in the CNS [71].…”
Section: Choice Of Aav Capsid Serotype and Promotermentioning
confidence: 99%
“…The recent approval of human AAV vector use in Europe and the USA has led to an array of gene therapy attempts in various clinical trials (Piguet et al, 2017;Axelsen and Woldbye, 2018;Hitti et al, 2019). The genetic approaches taken for PD treatment are largely neuro-regenerative in nature, and they are directed to halt neuronal cell death.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…The ability to target specific brain regions for gene therapy, as shown here, may prevent spreading Lewy pathology following α‐syn knockdown and also rescue failing neurons when combined with regeneration strategies using growth factors. Previous phases I and II clinical trials used viral vectors to express growth factors (neurturin, Glial cell line‐Derived Neurotrophic Factor (GDNF)) or increase dopamine biosynthesis (TH, aromatic L‐amino‐acid decarboxylase, and Guanosine triphosphate (GTP) cyclohydrolase‐1) . These trials involved small numbers of patients with fairly advanced disease and revealed only transient or modest benefits despite long‐lasting and well‐tolerated transgene expression.…”
Section: Discussionmentioning
confidence: 99%